Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1371/journal.pone.0240540
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced monocyte migratory activity in the pathogenesis of structural remodeling in atrial fibrillation

Abstract: Background and aims Pathophysiological roles of monocytes in atrial fibrillation (AF), particularly for the progression of structural remodeling of the left atrium (LA), remain elusive. This study examined the association between the characteristics of circulating and local monocytes and extent of structural remodeling in LA, gauged by LA size, in AF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…It has been suggested that macrophages play an important role in arrhythmogenesis since they can produce a number of cytokines which have been linked to cardiac remodeling. However, only recently a few studies have been published that clearly demonstrate specific macrophage-dependent mechanisms regulating physiologic conduction ( Hulsmans et al, 2017 ; Sugita et al, 2021 ; Simon-Chica et al, 2022 ) as well as electrical, structural, or autonomic remodeling leading to arrhythmias ( Monnerat et al, 2016 ; Sun et al, 2016 ; Yin et al, 2016 ; Fei et al, 2019 ; Hu et al, 2019 ; Liu et al, 2019 ; Lubos et al, 2020 ; Lyu et al, 2020 ; Miyosawa et al, 2020 ; Zhang et al, 2020 ; Hiram et al, 2021 ; Zhang et al, 2021 ) ( Figure 2 ).…”
Section: Cardiac Macrophages Mediate Arrhythmogenesis By Promoting Ca...mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that macrophages play an important role in arrhythmogenesis since they can produce a number of cytokines which have been linked to cardiac remodeling. However, only recently a few studies have been published that clearly demonstrate specific macrophage-dependent mechanisms regulating physiologic conduction ( Hulsmans et al, 2017 ; Sugita et al, 2021 ; Simon-Chica et al, 2022 ) as well as electrical, structural, or autonomic remodeling leading to arrhythmias ( Monnerat et al, 2016 ; Sun et al, 2016 ; Yin et al, 2016 ; Fei et al, 2019 ; Hu et al, 2019 ; Liu et al, 2019 ; Lubos et al, 2020 ; Lyu et al, 2020 ; Miyosawa et al, 2020 ; Zhang et al, 2020 ; Hiram et al, 2021 ; Zhang et al, 2021 ) ( Figure 2 ).…”
Section: Cardiac Macrophages Mediate Arrhythmogenesis By Promoting Ca...mentioning
confidence: 99%
“…Cardiac inflammatory responses e.g., in the context of myocardial infarction (MI) or heart failure (HF), are thought to crucially contribute to the proarrhythmic remodeling resulting in the development of vulnerable substrates in the heart ( Engelmann and Svendsen, 2005 ; Francis Stuart et al, 2016 ). Recently, studies have revealed the various roles played by immune cells, especially macrophages, in the maintenance of cardiac homeostasis ( Hulsmans et al, 2017 ; Sugita et al, 2021 ; Simon-Chica et al, 2022 ) and—if disrupted—the development of cardiac arrhythmias ( Monnerat et al, 2016 ; Sun et al, 2016 ; Yin et al, 2016 ; Fei et al, 2019 ; Hu et al, 2019 ; Liu et al, 2019 ; Lubos et al, 2020 ; Lyu et al, 2020 ; Miyosawa et al, 2020 ; Zhang et al, 2020 ; Hiram et al, 2021 ; Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through bioinformatics analysis, Gang Fan et al found that the expression of CCR2 was elevated in AF patients [ 43 ]. Miyosawa et al reported that the protein level of CCR2 was higher in isolated monocytes of AF patients whose left atrial diameter was larger [ 44 ]. Taken together, these reports are in agreement with our current demonstration that CCR2 , as a hub gene, was overexpressed in both NAFLD and AF datasets.…”
Section: Discussionmentioning
confidence: 99%
“…For example, monocyte activation especially the enhanced migration ability plays a vital role in the pathogenesis of progression in atrial remodeling in AF patients. 8 The role of the competing endogenous RNA (ceRNA) network has attracted much attention in recent years. 9 As a novel type molecule with special biological functions, circRNAs can be used as microRNA (miRNA) sponge to competitively bind miRNAs, modulate alternative splicing, and regulate the expression of parental genes.…”
Section: Introductionmentioning
confidence: 99%